Dead weight loss associated with economic efficiency use of esticides in Indonesian rice production - Joko Mariyono (Universitas Islam Indonesia, 2014)
This paper analyses the efficient use of pesticides by internalizing the costs of externality, and estimates the monetary value of welfare loss. The benefit of pesticide use is estimated using a production function, and the economic value of the adverse impact on human health and the environment are represented by a health cost and consumers’ willingness to pay for a kg reduction in pesticide use. To estimate the benefit of pesticides, the paper uses farm level crosssectional and time series data set on rice production. The results indicate low efficiency of using pesticide. This means that totally banning the use of pesticides is economically inefficient.